Cumulative Fluid Balance during Extracorporeal Membrane Oxygenation and Mortality in Patients with Acute Respiratory Distress Syndrome - Li-Chung Chiu; Li-Pang Chuang; Shih-Wei Lin; Yu-Ching Chiou; Hsin-Hsien Li; Yung-Chang Chen; Yu-Jr Lin; Chee-Jen Chang; Feng-Chun Tsai; Ko-Wei Chang; Han-Chung Hu; Chung-Chi Huang; et al. (Membranes, 2021)
Extracorporeal membrane oxygenation (ECMO) is considered a salvage therapy in cases of severe acute respiratory distress syndrome (ARDS) with profound hypoxemia. However, the need for high-volume fluid resuscitation and blood transfusions after ECMO initiation introduces a risk of fluid overload. Positive fluid balance is associated with mortality in critically ill patients, and conservative fluid management for ARDS patients has been shown to shorten both the duration of mechanical ventilation and time spent in intensive care, albeit without a significant effect on survival. Nonetheless, few studies have addressed the influence of fluid balance on clinical outcomes in severe ARDS patients undergoing ECMO. In the current retrospective study, we examined the impact of cumulative fluid balance (CFB) on hospital mortality in 152 cases of severe ARDS treated using ECMO. Overall hospital mortality was 53.3%, and we observed a stepwise positive correlation between CFB and the risk of death. Cox regression models revealed that CFB during the first 3 days of ECMO was independently associated with higher hospital mortality (adjusted hazard ratio 1.110 [95% CI 1.027–1.201]; p = 0.009). Our findings indicate the benefits of a conservative treatment approach to avoid fluid overload during the early phase of ECMO when dealing with severe ARDS patients.